How Should Student Behave? A Legal Ethics and Policy towards Nationalism and Anti-Radicalism Characters - Rodiyah, Rodiyah; Laskarwati, Batari; Masyhar, Ali; Waspiah, Waspiah (Universitas Negeri Semarang, 2019)
The university has become an important place in the cultivation of character for generations in many countries. Many universities in the world also apply a variety of systems in making policies to shape the character of campus communities, including students. This study aims to analyze legal and ethical policies for students in fostering an attitude of nationalism and anti-radicalism. This study also aims to describe the various forms of implementation of student ethics policies that are applied in the Faculty of Law, Semarang State University, Indonesia. This study uses a qualitative method with direct data collection through observation and interviews. This study bases its analysis on the theory of the operation of Lawrence M Friedman's law. The results of this study indicate that legal and ethical policies for students are interpreted by a variety of different interpretations both between managers and students. Various cases of inequality of perception lead to pros and cons. However, this research proves that the implementation of legal ethics and student character policies have been regulated in various rules, both at the national level (ministerial regulation), university level (rector regulation), and faculty level (dean regulation) all of which emphasize on forming attitudes nationalism and anti-radicalism.